Embryonic development grand challenge: crosslinking advances - Brand-Saberi, Beate (Frontiers in Cell and Developmental Biology, 2024)
Research on embryonic development is entering into a new era. As a traditionally descriptive discipline within anatomy, embryologists have formed international consortia and digitized important histological collections for preservation and open access. Embryonic development has recently received a wider attention in context with temporo-spatial transcriptomics at single cell level. These can be expected to fuel the realization of the transdisciplinary significance of efforts to decipher embryonic development. Addressing its complexities encompasses a wealth of challenges that intersect across the domains of science, society, and politics underlining its outstanding importance as well as its inherently interdisciplinary nature. The challenges of this field are by no means confined to understanding the intricate biological mechanisms but also have humanitarian implications. To fully appreciate the mechanisms underlying human development, principles of embryogenesis have predominantly been analyzed employing animal models which allow us to broaden our view on developmental processes. As a result of recent pioneering work and technical progress centered around stem cell-based 3D approaches, we are entering into a historical new phase of learning about mammalian embryonic development. In vertebrates, a growing concern now focuses the reduction of animal experimentation. This perspective article outlines the major challenges in this amazing field that offer an enormous potential for basic biomedical sciences as well as related translational approaches if they are tackled in a multidisciplinary discourse.